2005
DOI: 10.1111/j.1365-2648.2005.03623.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic working relationships with people with schizophrenia: literature review

Abstract: Therapeutic relationships are necessary but not sufficient to enable change when working with people with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 54 publications
3
125
1
6
Order By: Relevance
“…The researchers found no marked difference in outcome between the two treatment modes; there were, however, significant findings in relation to the therapeutic alliance which led the researchers to conclude that "the therapeutic alliance is not only a prerequisite for therapeutic work, but often may be the main vehicle of change" (Horwitz, 1974, p. 254-255). Moreover, the findings of an early review (Horvath & Symonds, 1991), which provided significant empirical support for the power of the therapeutic relationship, has been replicated in more recent reviews (Hewitt & Coffey, 2005;Horvath et al, 2011;Martin et al, 2000).…”
mentioning
confidence: 82%
“…The researchers found no marked difference in outcome between the two treatment modes; there were, however, significant findings in relation to the therapeutic alliance which led the researchers to conclude that "the therapeutic alliance is not only a prerequisite for therapeutic work, but often may be the main vehicle of change" (Horwitz, 1974, p. 254-255). Moreover, the findings of an early review (Horvath & Symonds, 1991), which provided significant empirical support for the power of the therapeutic relationship, has been replicated in more recent reviews (Hewitt & Coffey, 2005;Horvath et al, 2011;Martin et al, 2000).…”
mentioning
confidence: 82%
“…The therapeutic relationship is a reliable predictor of patient outcomes in mainstream psychiatric care. 23,24 Strong, collaborative, working alliances between case managers and people with long-term mental health difficulties have been shown to reduce symptoms, improve levels of functioning and social skills, promote quality of life, enhance medication compliance and raise levels of satisfaction with care received. 25 Yamashita et al 26 describe negotiating care within a trusting relationship as key in case management and this relationship may influence users' perceptions of stigma.…”
Section: Objective(s)mentioning
confidence: 99%
“…Services of support and treatment that is directed toward persons with SMI take place within a wealth of organizational contexts such as psychiatric inpatient care, community mental health services and support provided in people's homes [4]. Despite of these differences in context, it has been indicated that the relationship to professionals can be associated with a more positive outcome also within these kinds of services [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%